A proteção deficiente da vítima no Processo Penal: uma análise da omissão legislativa à luz da dignidade da pessoa humana - Souza Junior, Adalberto Ferreira de (2024)
The Brazilian legal system lacks standards that guarantee effective protection for victims of crimes. Although there is specific and effective protection in relation to some specifically considered victims, in general, victims do not have their human dignity preserved by the law. Women involved in situations of domestic and family violence are subject to law n. 11.340/2006 modern and effective protection mechanisms. Elderly people, moreover, find broad protection of their rights in law n. 10.741/2003. Finally, we can cite the example of children and adolescents, who also have unrestricted legal protection through law n. 8.069/1990. It can be seen, therefore, that the Brazilian legislator sought to protect some victims specifically considered according to their age or gender and their greater or lesser vulnerability in society. However, they forgot about victims who do not fall under these and other laws. The international scenario shows that since the 1940s there has been a concern with the protection of victims of crimes, and after the two World Wars, a historic movement for human rights began, called victimological, responsible for subsequently triggering a phase of rediscovery of the victim in history. After numerous international congresses around the world in which the rights of victims of crimes were effectively debated, the UN mobilized and took the initiative to draw up a formal document that specifically dealt with the rights of victims of crimes, and in 1995, after decades oblivion, the text was approved by the UN General Assembly under the title Declaration of Basic Principles of Justice Relating to Victims of Crime and Abuse of Power (Resolution n. 40/34, of 29-11-1985). Even though the aforementioned resolution was approved before the promulgation of the 1988 Brazilian Constitution, the constituents of our “citizen charter” did not pay attention to the debate about the effective protection of the human rights of victims of crimes and, consequently, did not have standards constitutional provisions that guaranteed protection consistent with the implementation of these human rights, already established at the international level. Only today, in the year 2023, in Brazil do we have a bill (PL 3.890/2020) being debated in the National Congress regarding the rights of victims, called “Victim Statute”, which seeks to protect rights of protection, participation and information hitherto unpublished in the legal system, specifically in the Brazilian criminal process. Even though this bill exists to guarantee the introduction of standards guaranteeing the rights of victims of crimes in Brazil, the text deserves a greater breadth and pluralization of the debate, in order to improve protection institutes and ensure that the standards contained therein are in accordance with the human dignity of victims of crimes